Iklim Organisasi dan Turnover Intention Perawat: Mediasi Kepuasan Kerja - Romauli Ervanny Goria Siallagan; Khairunnisa Batubara (JURNAL WACANA KESEHATAN, 2026)
Because it can affect both the stability of the nursing workforce and the quality of care, turnover intention among nurses is a critical issue. Thus, the purpose of this study is to examine how work satisfaction and organizational climate affect nurses' intentions to leave their jobs. This study employed a cross-sectional, non-experimental quantitative design. 150 nurses who worked at a Type C Private Hospital in Medan City participated in the study. A standardized questionnaire was used to gather data on organizational climate, job satisfaction, and turnover intention all at the same time. Multiple linear regression was used to evaluate the data in order to ascertain how independent variables contributed to turnover intention. The findings of the analysis revealed a coefficient of determination of 0.485, which indicates that work satisfaction and organizational climate account for 48.5% of the variation in turnover intention, while other factors outside the research model account for 51.5%. These results show that work satisfaction and organizational climate have a big impact on nurses' intentions to leave their jobs. The study concludes that lowering turnover intention can be achieved by enhancing a favorable workplace culture and high job satisfaction. To lower turnover intention and raise the standard of nursing care, hospitals are encouraged to bolster organizational support mechanisms and enhance nurse job satisfaction.